2020
DOI: 10.1002/bkcs.12175
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐catalyzed Aerobic Benzannulation of Pyrazoles with Alkynes

Abstract: As an alternative to a stoichiometric metal oxidant, oxygen was used as an oxidant for Pd‐catalyzed annulation reactions of pyrazoles with internal alkynes. The addition of sodium acetate and acetic acid was critical for stabilizing the Pd system. This green approach allowed the preparation of indazoles from readily available parent pyrazoles in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Unless an aryl group is installed at the nitrogen atom of pyrazole, we found that Pd-catalyzed, Cumediated benzannulation of pyrazoles occurred to afford indazole compounds (Scheme 11D). 60,61 In addition to a commonly employed stoichiometric metal oxidant, Cu(OAc) 2 • H 2 O, for benzannulation reactions, oxygen can be used as a green oxidant in the presence of sodium acetate and acetic acid. This aerobic method is extended to the benzannulation of functionalized furans and pyrroles with internal alkynes.…”
Section: Pyrazolementioning
confidence: 99%
“…Unless an aryl group is installed at the nitrogen atom of pyrazole, we found that Pd-catalyzed, Cumediated benzannulation of pyrazoles occurred to afford indazole compounds (Scheme 11D). 60,61 In addition to a commonly employed stoichiometric metal oxidant, Cu(OAc) 2 • H 2 O, for benzannulation reactions, oxygen can be used as a green oxidant in the presence of sodium acetate and acetic acid. This aerobic method is extended to the benzannulation of functionalized furans and pyrroles with internal alkynes.…”
Section: Pyrazolementioning
confidence: 99%
“…β-Ketonitriles are highly valuable motifs in organic synthesis because they can be readily converted to a variety of heterocyclic compounds, such as azoles, 1 pyrroles, 2 furans, 3 dihydropyridazines, 2 thiophenes, 4 imidazo[1,2- a ]pyridines, 5 2-pyridones, 6 and dioxapropellanes 7 as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%